Ordered Pt5fe2co2la Quaternary Alloy: A Breakthrough Catalyst for Enhanced Oxygen Reduction in Fuel Cells - Herrera-Diaz, F; Herrera-Diaz, F (American Chemical Society, 2025)
This study presents the development of an ordered Pt5Fe2Co2La/C quaternary alloy electrocatalyst for enhanced ORR (oxygen reduction reaction) performance in low-temperature fuel cells. The electrocatalysts were synthesized using a modified molten-salt technique and analyzed by the XRD (X-ray diffraction), TEM (transmission electron microscopy), and electrochemical methods. The Pt5Fe2Co2La/C electrocatalyst exhibited a 15-fold enhanced specific and mass activity compared to that of commercial Pt/C, attributed to its ordered alloy structure, lattice contraction, and synergistic effects among the constituent elements. Also, an exceptional durability was observed with high activity maintained up to 30,000 potential cycles before a gradual decline. The CO stripping voltammetry indicated improved CO tolerance and surface smoothening during stability testing. Further, in the single stack fuel cell testing, the fabricated electrocatalyst achieved a maximum of 1.86 W/cm2peak power density at 4.32 A/cm2current density in H2/O2conditions. The incorporation of lanthanum into the PtFeCo system resulted in a more effective and durable ORR catalyst. This quaternary alloy approach presents a promising direction for developing high-performance, platinum-efficient catalysts for fuel cell applications, emphasizing the potential of multielement alloy systems in addressing the critical challenges in electrocatalysis. © 2025 American Chemical Society